(untitled) (KULT_online, 2023)
Cartooning China: Punch, Power & Politics in the Victorian Era by Amy Matthewson provides various insights into the relationship between the famous British magazine Punch and Sino-British politics in the Victorian era. By contextualizing Punch’s cartoons and textual satires of China and the Chinese with the specific history of Sino-British politics, Matthewson argues that Punch played an important role in constructing a fixed idea of China and the Chinese in the British popular imagination, which reveals British self-perception and its role in the world.